Similar risk of ACL graft revision for alpine skiers, football and handball players: the graft revision rate is influenced by age and graft choice - Ekeland, A.; Engebretsen, L.; Fenstad, A. M.; Heir, S. (British Journal of Sports Medicine, 2020)
The risk of graft revision following ACL reconstruction may depend on the sport type the individuals are engaged in. The purpose of this study was to report the ACL graft revision rate in alpine skiers, football and handball players.